Effect of metacognitive online reading comprehension strategies on students’ comprehension achievement in the digital era / Saripah Sinas ... [et al.] - Sinas, Saripah; Narasuman, Suthagar; Sim, Sandra Phek-Lin; Issa, Rapeah; Singki, Eliza Embau (Universiti Teknologi MARA, 2024)
This study aimed to examine the effects of metacognitive online reading comprehension strategies (MORCS) on students’ online comprehension achievement as they read online texts that incorporate hyperlinks or webpages. This study examined the process that students engage in while using MORCS to read online texts and whether there is an improvement in students’ comprehension achievement in the digital era. The samples involved thirty technical skills students assigned to treatment class for an experiment. In class, students were taught how to use MORCS as they attempted comprehension tasks given on this link: www.readtheory.com. The MORCS questionnaire was distributed to all samples at the beginning of treatment, and followed by a pre-test was distributed to all the samples via a link to check on their existing comprehension performance. After completing the treatment, a post-test was administered to all the samples for responses by giving them a link. The data were analysed using SPSS software version 24.0. The findings indicated that most students engaged with strategies such as clicking on keywords, scrolling up and down on the text, using the e-dictionary for word meanings, rereading, and using Google translation for words or phrases and pictures, visual aids, or sounds to understand the online text. Others used videos or audio to support their reading for better understanding. The test results showed that after the intervention, there was an improvement in the students’ online comprehension achievement. Pedagogical implications and future research were also included in this study.